“Efecto de hongos microorízicos arbusculares nativos sobre el nematodo agallador de raices (meloidogyne spp.) en plantones de café (coffea arabica) variedad caturra en la región de San Martín - Chinchay Rubio, Decny Omar (2016)
Nowadays the use of microorganisms in agricultura is one of the alternativa solutions to reduce the use of chemicals products. The arbuscular mycorrhizal fungi (AMF) are soil fungi, which form mutualistic symbiosis with the roots of most plants, including the coffee, providing excellent benefits. The objective of this research was to determine the effect of different sources of inoculum of nativa AMF on root-knot nematode (Meloidogyne spp.) in coffee seedlings (Coffea arabica) variety caturra in the region San Martin. lt was used a completely randomized design (CRD) with 11 treatments (9 inoculum sources of native AMF + 2 witnesses) and 3 repetitions. To determine the antagonistic effect between these two organisms, 1500 spores were inoculated per plant of each one of the different sources of inoculum using a sterile substrate and after 140 days each plant were infested with 2000 eggs + J2 Meloidogyne spp. per plant. Plant height was assessed 15 days after infestation (001) and other variables were assessed 90 001. Ouring the process, the analysis of variance and Tukey's test (a= 0.05) was performed for all variables studied. The treatments T2 (4.75%), T8 (4.71 %) and T9 (5.14%) showed good results in controlling Meloidogyne spp. and the other study variables.